DEVELOPMENT AND EVALUATION OF A MODULAR HYDROPONICS WITH PELTIER COOLING SYSTEM FOR ROMAINE (Lactuca sativa) PRODUCTION - Marcelo, Kyla; Sulit, Meriam; Gatchalian, Shiela Marie; Villaroman, Cresan Joy; Cuevas, Cherry Mae (Agrofarm: Jurnal Agroteknologi, 2025)
This study evaluated the efficacy of the fabricated modular hydroponics system integrated with a Peltier module as rootzone cooling device to enhance romaine lettuce production. Two treatments set-ups with identical modular hydroponics were compared, the conventional lettuce production without rootzone cooling (Treatment 1) and with rootzone cooling (Treatment 2). The nutrient solution was maintained between 20 to 22 ºC. results if the statistical analysis using paired samples t-Test demonstrated significant differences at 5% level for yield performances. The analysis comparing the weight difference between the two treatments yielded a t-statistic of 2.654 with a p-value of 0.0139, where Treatment 2, significantly outperformed Treatment 1 in yield and efficiency. The final yield was 1390grams, significantly higher that Treatment 2, 1159grams. Economic feasibility yield a benefit-to-cost ration of 1.85 and a return on investment of less that 2 years, justifying the P12,828.76 cost of initial investment. The results confirm that the integration of Peltier module in rootzone temperature management is a robust and economically viable strategy for maximizing the yield of romaine lettuce in modular hydroponics.